Method for transforming ternary lithium battery black powder positive electrode and repairing and regenerating graphite negative electrode
By mixing the black powder of the retired ternary lithium battery with concentrated sulfuric acid and microwave heat treatment, the problems of high energy consumption and low efficiency in the recycling process of lithium battery in the prior art are solved, and the effect of efficient recycling of valuable metals and deep purification and repair of recycled graphite is achieved.
Patent Information
- Application Number
- CN202411862834.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-12-17
AI Technical Summary
The prior art has high energy consumption, low efficiency and pollution problems in the recycling of valuable metals and graphite in retired lithium batteries, especially in reducing acid leaching and high temperature heat treatment.
By fully mixing the black powder of the retired ternary lithium battery with concentrated sulfuric acid and microwave heat treatment in the microwave reactor, the sulfurization transformation of the ternary positive electrode material and graphitization repair of graphite are achieved, and then the valuable metal and recycled graphite are obtained through water immersion and subsequent treatment.
It realizes efficient recycling of valuable metals and deep purification and repair of recycled graphite in short time and at lower temperatures, reducing energy consumption and improving recovery rate, and has good industrial prospects.
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of solid waste resources and waste battery recycling, and specifically relates to a method for ternary lithium battery black powder positive electrode conversion and coordinated graphite negative electrode repair and regeneration. Background Art
[0002] Retired lithium batteries are rich in strategic resources such as lithium, nickel, cobalt, copper, and graphite, and their content is much higher than that of primary mineral resources. However, retired lithium batteries also contain toxic substances such as organic matter, fluorine, and phosphorus, which may harm the environment. Therefore, efficient and green recycling of strategic resources in retired lithium batteries is crucial.
[0003] Valuable metals such as lithium, nickel, cobalt, and manganese in retired lithium batteries are generally leached into a solution through reduction acid leaching, and then purified and extracted to obtain metal products. A reducing agent needs to be added during the reduction acid leaching process, and because the structure of the ternary material is relatively stable, the required acid concentration is high, the reagent cost of the leaching process is high, and the leaching efficiency is low. Patent 201510007518.2 proposes a method for recovering metals from waste nickel cobalt manganese lithium batteries. The retired lithium battery positive electrode powder is mixed with potassium hydrogen sulfate in a certain proportion and then roasted, and the roasted product is leached with water. This method converts lithium, nickel, cobalt, and manganese in the positive electrode powder into sulfates, and then the valuable metals can be leached out by water leaching. No reducing agent or inorganic acid needs to be added during the process, but the price of potassium hydrogen sulfate is relatively high, and potassium ions are introduced, which will have an adverse effect on the purification of subsequent products.
[0004] On the other hand, the recycling of waste graphite in retired lithium batteries has also received great attention in recent years. At present, strong acid is generally used to leach out the metal impurities, and then the damaged structure is repaired by high-temperature heat treatment (1500-2500°C), because the whole process consumes a lot of acid and energy, and direct acid leaching cannot achieve deep purification. Patent 201910090383.9 discloses a method for recycling silicon-containing waste graphite in lithium batteries. After mixing the waste graphite with concentrated sulfuric acid, a sulfuric acid aging reaction is carried out in a muffle furnace at a temperature of about 250°C. After aging, sulfuric acid leaching is used to remove metal impurities, and finally vacuum roasting is carried out at 1500°C to obtain graphite for regenerated batteries. The impurity removal effect of this waste graphite recovery method is acceptable, but the heat treatment temperature is high, the reaction time is long, and the energy consumption is high. Summary of the invention
[0005] In view of the shortcomings of the above-mentioned prior art, the present invention provides a method for economically and efficiently recovering valuable metals and waste graphite in waste ternary lithium batteries. The method has a simple process, low energy consumption, and a high recovery rate of valuable metals. The waste graphite can be deeply purified and efficiently repaired and regenerated, and has good industrial prospects.
[0006] A method for ternary lithium battery black powder positive electrode conversion and coordinated graphite negative electrode repair and regeneration, the method comprising: pre-treating retired ternary lithium batteries to obtain ternary lithium battery black powder (mixed powder of nickel, cobalt and manganese ternary positive electrode and graphite negative electrode), fully mixing the black powder with a certain amount of concentrated sulfuric acid, and then placing the mixed material in a microwave reactor for microwave heat treatment to achieve sulfation transformation of nickel, cobalt and manganese in the ternary positive electrode material to generate metal sulfate. The reaction principle can be described as follows:
[0007] LiNi x Co y Mn z O 2 +H 2 SO 4 →Li 2 SO 4 +NiSO 4 +CoSO 4 +MnSO 4
[0008] On the other hand, transition metal salts have the function of catalyzing graphitization, that is, the graphitization transformation of carbon materials can be achieved at a temperature of about 1000°C. Based on this, under the catalytic action of nickel, cobalt, and manganese sulfates in this method, the damaged structure in the waste graphite can be transformed and repaired into graphitization. In addition, since graphite itself is a strong microwave absorbing material, it can heat up quickly and generate high-temperature hot spots during microwave heating, which is more conducive to the sulfation reaction and catalytic graphitization.
[0009] After microwave heat treatment, water immersion is used to obtain a water immersion liquid containing lithium, nickel, cobalt and manganese and water-immersed graphite slag; the water immersion liquid is recovered to obtain a metal sulfate product; the water-immersed graphite slag is fully washed and dried to obtain battery-grade regenerated graphite.
[0010] A method for ternary lithium battery black powder positive electrode conversion and coordinated graphite negative electrode repair and regeneration, comprising the following steps:
[0011] (1) After the retired ternary lithium-ion batteries are subjected to a pretreatment step, ternary lithium battery black powder is obtained;
[0012] (2) Thoroughly mix the black powder with a certain amount of concentrated sulfuric acid;
[0013] (3) placing the mixed material into a microwave reactor for sufficient microwave heat treatment;
[0014] (4) stirring and leaching the product after microwave heat treatment in an aqueous solution to obtain a water extract containing lithium, nickel, cobalt, and manganese and water-soaked graphite slag; the water extract is subjected to a post-treatment step to obtain nickel sulfate, cobalt sulfate, manganese sulfate, and lithium carbonate products;
[0015] (5) The water-immersed graphite slag obtained in step (4) is fully washed with water and then dried to obtain a battery-grade regenerated graphite product.
[0016] Furthermore, in step (1), the pretreatment includes steps such as discharging, disassembling, crushing, and screening.
[0017] Furthermore, in step (2), the molar ratio of sulfuric acid in concentrated sulfuric acid to the sum of lithium, nickel, cobalt and manganese in black powder is 1 to 1.5 times.
[0018] Furthermore, in step (3), the microwave heat treatment temperature is controlled to be 700-800° C. and the heat treatment time is 20-60 minutes.
[0019] Furthermore, in step (4), the post-treatment steps of the water extract include purification, extraction separation, lithium carbonate precipitation, etc.
[0020] Furthermore, in step (4), during stirring leaching, the liquid-to-solid ratio is 3 to 10 mL / g, the leaching time is 0.5 to 3 h, and the leaching temperature is 10 to 50°C.
[0021] Furthermore, in step (5), the product is dried at 250-400°C.
[0022] For example, the method of ternary lithium battery black powder positive electrode conversion and coordinated graphite negative electrode repair and regeneration described in the present invention includes the following steps:
[0023] (1) After the retired ternary lithium-ion batteries are subjected to pretreatment steps such as discharging, disassembling, crushing, and screening, ternary lithium battery black powder is obtained;
[0024] (2) fully mixing the black powder with a certain amount of concentrated sulfuric acid, wherein the molar ratio of sulfuric acid in the concentrated sulfuric acid to the sum of lithium, nickel, cobalt and manganese in the black powder is 1 to 1.5 times;
[0025] (3) placing the mixed material into a microwave reactor for full microwave heat treatment, wherein the heat treatment temperature is controlled at 700 to 800° C. and the heat treatment time is 20 to 60 minutes;
[0026] (4) stirring and leaching the product after microwave heat treatment in an aqueous solution to obtain a water extract containing lithium, nickel, cobalt, and manganese and water-soaked graphite slag; the water extract is subjected to post-treatment steps such as purification, extraction separation, and lithium carbonate precipitation to obtain nickel sulfate, cobalt sulfate, manganese sulfate, and lithium carbonate products;
[0027] (5) The water-soaked graphite slag obtained in step (4) is fully washed with water and then dried at 250-400° C. to obtain a battery-grade regenerated graphite product.
[0028] Wherein, during the stirring leaching in step (4), the liquid-to-solid ratio is 3-10 mL / g, the leaching time is 0.5-3 h, and the leaching temperature is 10-50° C.
[0029] The present invention also relates to a combination of nickel sulfate, cobalt sulfate, manganese sulfate, lithium carbonate products and battery-grade regenerated graphite products obtained by the method of ternary lithium battery black powder positive electrode conversion and coordinated graphite negative electrode repair and regeneration as described above.
[0030] Beneficial Effects
[0031] (1) In the present invention, retired ternary lithium battery black powder is fully mixed with concentrated sulfuric acid and then subjected to microwave heat treatment. Due to the strong microwave absorption effect of the graphite material, lithium, nickel, cobalt, manganese and impurity elements in the ternary positive electrode material can be transformed into sulfates in a shorter time and at a lower temperature, and then the valuable metals can be effectively leached in the subsequent water immersion process, and the impurities in the graphite can also be efficiently removed;
[0032] (2) In the present invention, the sulfates of nickel, cobalt and manganese have a catalytic graphitization effect on waste graphite. At the same time, under microwave heat treatment, the local temperature in the waste graphite can reach more than one thousand degrees Celsius, and its damaged structure can be effectively repaired and regenerated into a graphite negative electrode for batteries;
[0033] (3) The technical method of the present invention has a simple process, low energy consumption, and a high recovery rate of valuable metals. Waste graphite can be deeply purified and efficiently repaired and regenerated; that is, it realizes the efficient recovery of valuable metals and graphite in ternary lithium battery black powder, and has prospects for industrial application.
[0034] The present invention has been described in detail above, but the above embodiments are only illustrative in nature and are not intended to limit the present invention. In addition, this article is not limited by any theory described in the above prior art or invention content or the following examples. DETAILED DESCRIPTION
[0035] The present invention is further described below in conjunction with examples. It should be noted that the following examples are provided for illustrative purposes only and do not constitute a limitation on the scope of protection claimed for the present invention.
[0036] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.
[0037] Example 1
[0038] After the retired ternary lithium-ion battery is discharged, disassembled, crushed and sieved for pretreatment, the ternary lithium battery black powder is obtained and mixed with concentrated sulfuric acid. The amount of sulfuric acid in the concentrated sulfuric acid is 1.1 to the molar ratio of the sum of lithium, nickel, cobalt and manganese in the black powder. The mixed material is placed in a microwave reactor for microwave heat treatment. The heat treatment temperature is controlled at 700°C and the heat treatment time is 60 minutes. The product after microwave heat treatment is stirred and leached in an aqueous solution. The liquid-solid ratio is 3mL / g, the leaching time is 1h, the leaching temperature is 20°C, and the water leaching rate is: 98.4% lithium, 98.5% nickel, 97.9% cobalt, and 99.4% manganese. The water leaching liquid is purified, extracted, separated, and lithium carbonate precipitated to obtain nickel sulfate, cobalt sulfate, manganese sulfate, and lithium carbonate products. After the water-soaked graphite slag is fully washed with water, it is dried at 400°C to obtain regenerated graphite. The first charge capacity of the regenerated graphite is 345mAh / g, and the first coulomb efficiency is 91.8%.
[0039] Example 2
[0040] After the retired ternary lithium-ion battery is discharged, disassembled, crushed, and sieved for pretreatment, the ternary lithium battery black powder is obtained and mixed with concentrated sulfuric acid. The amount of sulfuric acid in the concentrated sulfuric acid is 1.5 to the molar ratio of the sum of lithium, nickel, cobalt, and manganese in the black powder. The mixed material is placed in a microwave reactor for microwave heat treatment, and the heat treatment temperature is controlled to be 800°C and the heat treatment time is 20 minutes. The product after microwave heat treatment is stirred and leached in an aqueous solution, with a liquid-solid ratio of 8mL / g, a leaching time of 2h, and a leaching temperature of 40°C. The water leaching rate is: 99.5% lithium, 97.6% nickel, 98.1% cobalt, and 99.5% manganese. The water leaching liquid is purified, extracted, separated, and lithium carbonate precipitated to obtain nickel sulfate, cobalt sulfate, manganese sulfate, and lithium carbonate products. After the water-soaked graphite slag is fully washed with water, it is dried at 300°C to obtain regenerated graphite. The first charge capacity of the regenerated graphite is 352mAh / g, and the first coulomb efficiency is 90.7%.
[0041] Example 3
[0042] After the retired ternary lithium-ion battery is discharged, disassembled, crushed, and pre-treated by screening, the ternary lithium battery black powder is fully mixed with concentrated sulfuric acid. The amount of sulfuric acid in the concentrated sulfuric acid is 1.3 to the molar ratio of the sum of lithium, nickel, cobalt, and manganese in the black powder. The mixed material is placed in a microwave reactor for microwave heat treatment, and the heat treatment temperature is controlled to be 750°C and the heat treatment time is 30 minutes. The product after microwave heat treatment is stirred and leached in an aqueous solution, with a liquid-solid ratio of 10mL / g, a leaching time of 3h, and a leaching temperature of 30°C. The water leaching rate is: 98.9% lithium, 98.7% nickel, 98.4% cobalt, and 98.9% manganese. The water leaching liquid is purified, extracted, separated, and lithium carbonate precipitated to obtain nickel sulfate, cobalt sulfate, manganese sulfate, and lithium carbonate products. After the water-soaked graphite slag is fully washed with water, it is dried at 250°C to obtain regenerated graphite. The first charge capacity of the regenerated graphite is 357mAh / g, and the first coulomb efficiency is 91.2%.
[0043] Comparative Example 1
[0044] After the retired ternary lithium-ion battery is discharged, disassembled, crushed, and screened for pretreatment, the ternary lithium battery black powder is fully mixed with concentrated sulfuric acid. The amount of sulfuric acid in the concentrated sulfuric acid is 1.1 to the molar ratio of the sum of lithium, nickel, cobalt, and manganese in the black powder. The mixed material is placed in a muffle furnace for treatment, and the heat treatment temperature is controlled at 700°C and the heat treatment time is 60 minutes. The heat-treated product is stirred and leached in an aqueous solution with a liquid-solid ratio of 3mL / g, a leaching time of 1h, and a leaching temperature of 20°C. The water leaching rate is: 91.3% lithium, 87.6% nickel, 84.2% cobalt, and 88.9% manganese. After the water-soaked graphite slag is fully washed with water, it is dried at 400°C to obtain regenerated graphite. The first charge capacity of the regenerated graphite is 306mAh / g, and the first coulomb efficiency is 83.8%.
[0045] It can be seen that compared with the prior art, the scheme of the present invention can transform lithium, nickel, cobalt, manganese and impurity elements in the ternary positive electrode material into sulfates in a shorter time and at a lower temperature by fully mixing retired ternary lithium battery black powder with concentrated sulfuric acid and then performing microwave heat treatment and other steps, and then effectively leaching valuable metals in the subsequent water immersion process, and at the same time can effectively repair and regenerate it into a graphite negative electrode for batteries; the obtained product has good charge specific capacity and first coulomb efficiency, etc., thereby realizing efficient recovery of valuable metals and graphite, etc. in the ternary lithium battery black powder.
[0046] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit them. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that the technical solutions described in the above embodiments may be modified, or some or all of the technical features thereof may be replaced by equivalents, without departing from the spirit and essence of the claims of the present invention; and these modifications or replacements are still within the scope defined by the claims of the present invention.
Claims
1. A method for ternary lithium battery black powder positive electrode conversion and coordinated graphite negative electrode repair and regeneration, characterized in that: The steps include: (1) After the retired ternary lithium-ion batteries are subjected to a pretreatment step, ternary lithium battery black powder is obtained; (2) Thoroughly mix the black powder with a certain amount of concentrated sulfuric acid; (3) placing the mixed material into a microwave reactor for sufficient microwave heat treatment; (4) stirring and leaching the product after microwave heat treatment in an aqueous solution to obtain a water extract containing lithium, nickel, cobalt, and manganese and water-soaked graphite slag; the water extract is subjected to a post-treatment step to obtain nickel sulfate, cobalt sulfate, manganese sulfate, and lithium carbonate products; (5) The water-immersed graphite slag obtained in step (4) is fully washed with water and then dried to obtain a battery-grade regenerated graphite product.
2. A method for converting the positive electrode of a ternary lithium battery black powder and coordinating the repair and regeneration of the graphite negative electrode as described in claim 1, further characterized in that in step (1), the pretreatment includes discharging, disassembling, crushing, and screening steps.
3. A method for converting the positive electrode of a ternary lithium battery black powder and repairing and regenerating the graphite negative electrode as described in claim 1, further characterized in that in step (2), the molar ratio of sulfuric acid in concentrated sulfuric acid to the sum of lithium, nickel, cobalt and manganese in the black powder is 1 to 1.5 times.
4. A method for converting a ternary lithium battery black powder positive electrode and coordinating the repair and regeneration of a graphite negative electrode as described in claim 1, further characterized in that in step (3), the temperature of the microwave heat treatment is 700-800°C.
5. A method for ternary lithium battery black powder positive electrode conversion and coordinated graphite negative electrode repair and regeneration as described in claim 1, further characterized in that in step (3), the treatment time of microwave heat treatment is 20 to 60 minutes.
6. A method for converting the positive electrode of a ternary lithium battery black powder and coordinating the repair and regeneration of the graphite negative electrode as described in claim 1, further characterized in that in step (4), the post-treatment step of the water immersion liquid includes purification, extraction separation, and lithium carbonate precipitation.
7. A method for ternary lithium battery black powder positive electrode conversion and coordinated graphite negative electrode repair and regeneration as described in claim 1, further characterized in that in step (4), the liquid-to-solid ratio during stirring leaching is 3 to 10 mL / g.
8. A method for ternary lithium battery black powder positive electrode conversion and coordinated graphite negative electrode repair and regeneration as described in claim 1, further characterized in that in step (4), the leaching time during stirring leaching is 0.5 to 3 hours.
9. A method for converting the positive electrode of a ternary lithium battery black powder and repairing and regenerating the negative electrode of a graphite battery as described in claim 1, further characterized in that in step (4), the leaching temperature during stirring leaching is 10 to 50°C.
10. A method for converting the positive electrode of a ternary lithium battery black powder and repairing and regenerating the negative electrode of a graphite battery as described in claim 1, further characterized in that in step (5), the mixture is dried at 250-400°C.
Citation Information
Patent Citations
Methods for recovering metals from spent nickel-cobalt-manganese lithium batteries
CN104466294B
Method for recovering silicon-containing waste graphite from lithium battery
CN109678144A
Method for recovering valuable elements from waste battery material smoke dust
CN117305605A